Pengembangan Karakter dan Peran Orang Tua, Guru, dan Pelajar dalam Mencapai Keberhasilan - Diana Puspita Kusuma Wardani (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Islamic education emphasizes character building and moral conduct (adab) as fundamental aspects of the learning process. This study is motivated by the importance of sincere intention, careful selection of teachers, and the synergistic roles of parents, teachers, and students in shaping students’ character and attaining the blessing of knowledge. This research aims to examine the concept of character development from the perspective of Shaykh az-Zarnuji as presented in Ta‘lim al-Muta‘allim, as well as to analyze the relational roles of parents, teachers, and students in achieving educational success within Islamic education. This study employs a qualitative approach using library research, with Ta‘lim al-Muta‘allim as the primary source and supported by relevant scholarly literature. Data were analyzed using content analysis techniques. The findings indicate that character development is achieved through sincere intention for the sake of Allah, selectivity in choosing knowledgeable and morally upright teachers, the cultivation of virtuous conduct toward oneself, teachers, and peers, and the optimal use of time through spiritual activities such as remembrance (dhikr), worship, supplication, and deliberation. Furthermore, the study highlights that educational success and the nobility of knowledge largely depend on the synergistic roles of parents as primary educators and role models, teachers as intellectual and moral guides, and students as learners who demonstrate humility and earnestness in seeking knowledge. The harmonious interaction among these three elements is a fundamental prerequisite for holistic character formation, noble conduct, and the attainment of blessed knowledge in Islamic education. Keywords: Character Development, Synergy, Parents, Teacher, Student